2014
DOI: 10.4300/jgme-d-14-00339.1
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Quality in Medical Education Research: A Consumer's View

Abstract: Background Despite an explosion of medical education research and publications, it is not known how medical educator consumers decide what to read or apply in their practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…1,8,9 Research has shown that consumers of medical education literature find the greatest value in novel, provocative research findings and methodologically sound research; other important features include relevance, feasibility, and connection to a conceptual framework. 21 Use of the MERSQI may enhance methodological quality in evaluating curricula and performing medical education research. 22 There are several limitations to our study.…”
Section: Discussionmentioning
confidence: 99%
“…1,8,9 Research has shown that consumers of medical education literature find the greatest value in novel, provocative research findings and methodologically sound research; other important features include relevance, feasibility, and connection to a conceptual framework. 21 Use of the MERSQI may enhance methodological quality in evaluating curricula and performing medical education research. 22 There are several limitations to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Education research is an important component of the advancement of any medical discipline, and recent publications have outlined a need for initiatives to improve the quality of education studies and support educators who wish to approach educational challenges, questions, and theory in a scholarly manner 19. Medical educators have reported being limited by the following: 1) time to develop and maintain research skills and engage in all phases of the research process; 2) funding to support time and provide research resources; 3) access to expertise for study design and statistical analyses; 4) access to mentors, both within and outside of emergency medicine (EM); and 5) a sense that education research does not result in extrinsic or intrinsic reward in our current educator paradigm 1012.…”
Section: Introductionmentioning
confidence: 99%
“…Education scholarship has seen steady growth throughout academic medicine over the past decade, and the field of emergency medicine (EM) is no exception . The 2012 Academic Emergency Medicine consensus conference “Education Research In Emergency Medicine: Opportunities, Challenges, and Strategies for Success” provided an essential roadmap for this movement, including recommendations for developing postgraduate training for aspiring EM education researchers, establishing a framework for education research networks to foster collaboration among institutions, and advocating for the creation and expansion of mechanisms for grant funded education .…”
mentioning
confidence: 99%